Hubungan Change of Direction Deficit Dengan Kecepatan Sprint Dan Daya Ledak Tungkai Pada Pemain Sepakbola Remaja - Zainuddin, M. Said; Usman, Arifuddin; Zakaria, Ahmad (Prodi Pendidikan Jasmani dan Olahraga, 2026)
This study aimed to examine the relationships between Change of Direction Deficit (CoDD), linear sprint speed, and lower limb tenaga in male youth soccer players. A correlational, cross-sectional design was employed. The sample consisted of 30 male soccer players aged 18–19 years from the Universitas Negeri Makassar team, who were engaged in structured training. The study was conducted on the Faculty of Sports Science (FIKK) soccer field between September and November 2025. Performance assessments included the 505 Change of Direction (CoD) test, a 20 m linear sprint test with 5, 10, and 20 m split times, and lower limb tenaga measured via a vertical jump test. CoDD was calculated as the difference between 505 CoD time and 10–20 m sprint time. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and Pearson’s correlation with a significance level of α = 0.05. The results indicated no significant relationships between CoDD and 5 m, 10 m, or 20 m sprint times (r = 0.134–0.188; p > 0.05), confirming that CoDD is dependent of linear sprint speed. In contrast, a significant negative correlation was found between CoDD and vertical jump height (r = -0.487; p = 0.006), suggesting that greater lower limb tenaga is associated with more efficient change of direction. These findings suggest that coaches should prioritize explosive leg training and utilize CoDD values as a tool for monitoring players' change-of-direction abilities. These findings support the use of CoDD as a specific indicator of change-of-direction ability in youth soccer players and highlight lower-limb tenaga development as a key component in training programs aimed at improving change-of-direction efficiency.